Effects of corporate tax reforms on SMEs' investment decisions under the particular consideration of inflation - Chang Woon Nam; Doina Maria Radulescu (Center for Economic Studies and ifo Institute (CESifo), 2005)
Corporate tax reforms carried out in EU countries since 1980 entail lower statutory tax rates and reductions in generous tax depreciation provisions. Several countries including the UK have reduced tax rates for SMEs. This study compares incentive effects of such reforms on the SMEs? investment decisions adopting simple present value model. Ceteris paribus tax rate and depreciation rule vary in the model simulation, while the application of historical cost accounting method in inflationary phases leads to fictitious increases in nominal net present value. Apart from the construction of international ranking, country- specific patterns of reform effects are also illustrated.
Keywords: H25; H32; 330; SMEs; corporate tax reform; investment decision; inflation; EU countries; Unternehmensbesteuerung; Steuerreform; Steuerwirkung; Klein- und Mittelunternehmen; Investition; Inflation; Schätzung; Deutschland